STUDENTS’ LISTENING COMPREHENSION PEFORMANCE IN THE MINI TALKS SECTION OF THE TOEFL (PBT) - Amanda, Aidil Fitra; Handayani, Fitri; Dwiputri, Risza (Asosiasi dosen IDEBAHASA KEPRI, 2025)
Listening comprehension is one of the essential skills tested in the TOEFL Paper-Based Test (PBT), and the Mini Talks section is often considered the most challenging. Students must concentrate on fast-paced monologues containing dense information and answer several questions at once. Observations and interviews revealed that many students failed to capture key details, lacked strategies to filter important information, and struggled to handle multiple questions within a short time. Based on these problems, this study aimed to describe the students’ listening ability and identify the difficulties they faced when answering Mini Talks questions in the TOEFL PBT. This study used a descriptive quantitative method. The participants were 16 eighth-semester students of the English Education Department at Universitas Mahaputra Muhammad Yamin, Solok, in the 2024/2025 academic year. Data were collected using a listening test focusing on the Mini Talks section, and the students’ scores were analyzed to determine their average performance and the easiest and most difficult question types. The results showed that the students’ average score in the Mini Talks section was 47.7, categorized as “fair.” The easiest question type was purpose (68.8%), while the most difficult was attitude and opinion (34.4%). The findings indicate that students had the most difficulty interpreting tone, making inferences, and identifying key information from audio played only once. This study suggests the need for more targeted listening practice and effective teaching strategies to improve students’ performance in the TOEFL PBT listening section.